SISTEM GROSS SPLIT DALAM KONTRAK PERTAMBANGAN MENURUT PASAL 33 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Wicaksono, Bimo Suryo; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This article aimed to analyze and to study the Minister of Energy, Resource, and Mineral’s Regulation Number 08 of 2017 about Gross Split in relation to Article 33 of 1945 Constitution. This normative law research was descriptive –analytical in nature. Technique of collecting data used was library study by examining documents and literatures used in this research. Technique of analyzing data used was normative qualitative one, studying by means of interpreting and constructing statement existing in legislation document. The result of research showed that gross split scheme in Minister of Energy, Resource, and Mineral’s Regulation Number 08 of 2017 was compatible to Article 33 of 1945 Constitution. Article 2 clause (1) of Minister of Energy, Resource, and Mineral’s Regulation Number 08 of 2017 governed that the ownership of natural resource remained to be on government’s hand until transfer period. In gross split profit sharing contract system, petroleum, gas, and natural resource belonged to State until transfer period; thus production profit sharing approved in the contract would be conducted in transfer period. Gross split could give more profit to the state because government should no longer reimburse contractor operating cost included into State Income and Expenditure Budget (APBN) so far.